Insilico Characterization Of Novel Ph20 Hyaluronidase Protein Sequences Of Murrah (Bubalus Bubalis) Bul (Applied Biological Research, 2016)
PH20 hyaluronidase proteins are members of Zona pellucida binding protein family. PH20 hyaluronidase is reportedly bifunctional i.e. have hyaluronidase  and sperm-zona binding activities. In this study, we performed insilico  characterization of novel PH20 protein using partial nucleotide sequences,  obtained from SNP genotyping of Bubalus bubalis bulls, by Sanger’s dideoxy  sequencingmethod. These gene sequences are novel and first time reported in  bubalis. Possible glycosylation and mannosylation patterns were also hyaluronidase sequences which appear responsible for its hyaluronidase activity.Further, thpotential tertiary structureofPH20 was deducedusingSwiss-Model server. The tertiary structure models of PH20 were validated by ProSA server and Ramachandran plots. The tertiary structure models of PH20 were further refined using KoBaMIN server and validatedbyPROCHECK, ProSA and Ramachandran plots. These structural models were assigned PMDB identifiers PM0080458 and PM0080459. Physico-chemical characterization revealed that B. bubalis PH20 hyaluronidase are more thermostable and more hydrophobic than that of cattle PH20 hyaluro-nidase. The functional annotations were further inferred using Gene Ontolgy based predictions. Present work on elucidated structure of PH20 predicts a reference model for functional genomics studies related to multifunctionality of PH20 hyaluronidase proteins with respect to genetic variants within the species or trans-species. The current work is the first preliminary insilico study on novel bubaline PH20 hyaluronidases.
Keywords: Gene ontology; glycosylation; homology modeling; PH20 hyaluronidase; zona pellucida binding protein